STRATEGI KELUARGA BATAK KARO DALAM MENYELENGGARAKAN KESENIAN GENDANG GURO-GURO ARON DI MANADO - Kartika Egia Ninta Br Sitepu (Universitas Sam Ratulangi, 2023)
Knowing the wealth of traditions in the Lake Toba area cannot be separated from the intangible heritage that has been authorized by the Ministry of Culture and Education. In the Batak Karo tradition, there are three intangible cultural heritages, for example (1) Guro-guro Aron, (2) Merdang Merdem, (3) Erpangir Ku Lau. In addition to Batak land, now Guro-guro Aron Drum has also been displayed in several regions in Indonesia, including in Cikopo, Yogyakarta, Manado, and others. This shows that the Batak Karo community is also very closely related to the world of art such as dancing, singing, and playing musical instruments. Music is one of the complementary instruments when the Batak Karo people perform the Guro-guro Aron Drum dance. This art still exists in Manado, and of course has adapted continuously in accordance with the interests of the dynamic Batak Karo community in keeping up with the times. That is, these changes and shifts in art occur in line with changes in Karo society in various aspects of life, let alone They are overseas. The performance of Guro-guro Aron Drum in Manado is not only the Batak Karo family who watches but all Batak in Manado and even Minahasa people also watch like the Batak Karo family who married Minahasa people. It is very likely that this Guro-guro Aron Drum performance, in addition to strengthening family ties, can also resolve disputes that occur in the Batak Karo family. Keywords: strategy, Batak Karo family, art Guro-guro Aron